Voluntary emission reduction market in China: development, management status and future supply. Issue 1 (2nd January 2019) - Zhou, Yi; Gu, Alun; Deng, Maozhi
ABSTRACT: The voluntary emission reduction (VER) trading mechanism has played an important role in China's seven pilot carbon markets. From a comprehensive review of the VER trading and offsetting mechanisms since 2013, this study analyses the quality management of the Chinese Certified Emission Reduction (CCER) in the pilot carbon markets, conducts a comparative analysis of the geographical and field distributions of proposed and registered projects and emission reductions and provides the CCER supply outlook for 2020 in the aspects of on record, project registration, emission reduction registration and emission reduction issuance. Results show that the potential number of CCER projects by 2020 will be 2, 864, 1, 047, 818, and 286 with the corresponding emission reductions amounting to 493, 212, 133, and 49 million tCO2 e, respectively. Although considerable progress has been made, China remains confronted with many challenges in developing the VER trading system. Accordingly, policy stability and continuity and guarding against market risks should be maintained to enable the system to play a substantial role in promoting ecological progress and green low-carbon development in China.